6, 7‐Dihydro‐5H‐1, 2, 4‐triazolo[3, 4‐b][1, 3, 4]thiadiazine Ring Cleavage and Tautomerism of the Products: Experimental and Theoretical Study. Issue 12 (25th March 2020) - Kolodina, Alexandra A.; Tsaturyan, Arshak A.; Galkina, Maria S.; Borodkina, Inna G.; Vetrova, Elena V.; Demidov, Oleg P.; Berezhnaya, Alexandra G.; Metelitsa, Anatoly V.
Abstract: Electronic effects of aryl substituents at the C(7)‐atom play a crucial role in the cleavage of a six‐membered ring of 6, 7‐dihydro‐5 H ‐[1, 2, 4]triazolo[3, 4‐ b ][1, 3, 4]thiadiazines. Our experiments show that electron‐withdrawing 2‐nitrophenyl and 4‐nitrophenyl groups promote the N−N‐bond cleavage, whereas a phenyl group and a bulky 4, 5‐dimethoxy‐2‐nitrophenyl substituent are favored for the C−S‐bond cleavage, affording novel triazole derivatives. UV‐vis, electrochemical, and dynamic NMR studies as well as DFT calculations of product's tautomeric equilibria were performed. Abstract : The cleavage mechanism of thiadiazine cycle, which is formed as intermediate in the reactions of coupling of aromatic aldehydes with benzyl halides via 4‐Amino‐4 H ‐1, 2, 4‐triazole‐3‐thiol, is described. The dependence of the reaction pathway on the nature of aryl substituents is established. The correlation of tautomerism and solvatochromism of products is determined.